Polymorphism, polytypism and modular aspect of compounds with the general formula A2M3(TO4)4 (A = Na, Rb, Cs, Ca; M = Mg, Mn, Fe3+, Cu2+; T = S6+, P5+): order–disorder, topological description and DFT calculations. Issue 1 (31st January 2022) - Aksenov, Sergey; Antonov, Andrey; Deyneko, Dina; Krivovichev, Sergey; Merlino, Stefano
Abstract : The replacement of Na + by alkali metal cations with larger ionic radii (Rb + and Cs + ) in compounds with the chemical formula A 2 Mg3 (SO4 )4 significantly changes the topology of the heteropolyhedral MT framework. Abstract : The crystal structure of Na2 Mn3 (SO4 )4 [unit‐cell parameters a = 14.8307 (18), b  = 9.9107 (18), c = 8.6845 (12) Å, space group Cmc 21 ] displays order–disorder (OD) character and can be described using the OD groupoid family, more precisely a family of OD structures built up by two types of non‐polar layers, with layer symmetry P ( m ) c 21 ( L 2 n +1 type) and P ( b ) cm ( L 2 n type) (category IV). A new hypothetical MDO2 polytype has been proposed and the geometry optimization demonstrates its reasonability as another possible stable polytype. Compounds Na2 Mn3– x Mg x (SO4 )4 with the unit‐cell parameters a ∼ 29.2–29.7 Å, b ∼ 9.5–9.9 Å, c ∼ 8.7 Å and space group Pbca can be described in terms of modularity as a sequence of A, S 1 and S 2 modules:…| AS 1 AS 2 AS 1 AS 2 |… or ( AS 1 AS 2 ), together with MDO1 ( AS 1 AS 1 ) and MDO2 ( AS 2 AS 2 ). The crystal structures of itelmenite, NaCaFe 3+ 3 (PO4 )4, and Ca2 MgFe 3+ 2 (PO4 )4 are crystal‐chemical isotypic to Na2 Mn3– x Mg x (SO4 )4 and should be considered as ( A * S 1 A * S 2 ) derivatives of the ( AS 1 AS 2 )‐type structure.